2020
DOI: 10.1111/adb.12918
|View full text |Cite
|
Sign up to set email alerts
|

Increases in endogenous progesterone attenuate smoking in a cohort of nontreatment seeking women: An exploratory prospective study

Abstract: Despite advances in prevention and treatment, cigarette smoking remains a leading cause of preventable death in the United States. Although men and women are equally likely to attempt to quit smoking cigarettes, women are far less likely to achieve abstinence both during and following cessation treatment. Recent evidence suggests that ovarian hormone levels may play a role in successful abstinence attempts in women smokers. The primary goal of this exploratory prospective observational study was to estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Participants that do not return saliva samples or with unusable samples will be replaced and the final sample of 45 will be based on those with complete and analyzed saliva samples. Daily home collection and storage procedures have been used in previous studies with excellent participant adherence and sample quality (Baker et al, 2021; Edler et al, 2007; Klump et al, 2008). Within‐person estrogen and progesterone will be calculated by subtracting the person mean from the daily value, then dividing the result by the person's standard deviation (person‐standardized daily hormone level) (Eisenlohr‐Moul et al, 2018; Klump et al, 2013; Martel et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Participants that do not return saliva samples or with unusable samples will be replaced and the final sample of 45 will be based on those with complete and analyzed saliva samples. Daily home collection and storage procedures have been used in previous studies with excellent participant adherence and sample quality (Baker et al, 2021; Edler et al, 2007; Klump et al, 2008). Within‐person estrogen and progesterone will be calculated by subtracting the person mean from the daily value, then dividing the result by the person's standard deviation (person‐standardized daily hormone level) (Eisenlohr‐Moul et al, 2018; Klump et al, 2013; Martel et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical research examining the influence of hormones on addiction processes is generally supportive of the animal literature ( Becker et al., 2017 ; Fattore et al., 2008 ; Wetherill et al., 2016 ). Research has shown that exogenously administered P decreases the positive subjective effects of combustible cigarette smoking and associated craving ( Sofuoglu et al., 2001 ), reduces smoking intensity as measured by puff volume ( Harrison et al., 2020 ), and higher within-person P levels predict reductions in the number of cigarettes smoked per day ( Baker et al., 2020 ). These studies and others ( DeVito et al., 2014 ; Mello, 2010 ; Schiller et al., 2012 ) suggest that P, of which levels are greatest relative to E during the mid-luteal phase of the menstrual cycle, may offer some protection over drug-seeking behavior and drug use.…”
Section: Introductionmentioning
confidence: 99%